Developmental and behavioral effects of postnatal amitraz exposure in rats - Palermo-Neto, J.; Sakaté, M.; Flório, J. C. (FapUNIFESP (SciELO), 1997)
The effects of postnatal amitraz exposure on physical and behavioral parameters were studied in Wistar rats, whose lactating dams received the pesticide (10 mg/Kg) orally on days 1, 4, 7, 10, 13, 16 and 19 of lactation; control dams received distilled water (1 ml/kg) on the same days. A total of 18 different litters (9 of them control and 9 experimental) born after a 21- day gestation were used. The results showed that the median effective time (ET50) for fur development, eye opening, testis descent and onset of the startle response were increased in rats postnatally exposed to amitraz (2.7, 15.1, 21.6 and 15.3 days, respectively) compared to those of the control pups (1.8, 14.0, 19.9 and 12.9 days, respectively). The ages of incisor eruption, total unfolding of the external ears, vaginal and ear opening and the time taken to perform the grasping hindlimb reflex were not affected by amitraz exposure. Pups from dams treated with amitraz during lactation took more time (in seconds) to perform the surface righting reflex on postnatal days (PND) 3 (25.0 ±2.0), 4 (12.3 ± 1.2) and 5 (8.7 ± 0.9) in relation to controls (10.6 ± 1.2; 4.5 ± 0.6 and 3.4 ± 0.4, respectively); the climbing response was not changed by amitraz. Postnatal amitraz exposure increased spontaneous motor activity of male and female pups in the open-field on PND 16 (140± 11)and 17(124± 12), and 16 (104±9), 17 (137 ± 9) and 18 (106 ± 8), respectively. Data on spontaneous motor activity of the control male and female pups were 59 ± 11 and 69 ± 10 for days 16 and 17 and 49 ± 9, 48 ± 7 and 56 ± 7 for days 16, 17 and 18, respectively. Some qualitative differences were also observed in spontaneous motor behavior; thus, raising the head, shoulder and pelvis matured one or two days later in the amitraz- treated offspring. Postnatal amitraz exposure did not change locomotion and rearing frequencies or immobility time in the open-field on PND 30, 60 and 90. The present findings indicate that postnatal exposure to amitraz caused transient developmental and behavioral changes in the exposed offspring and suggest that further investigation of the potential health risk of amitraz exposure to developing human and animal offsprings may be warranted.
Keywords: Amitraz; Behavioral teratology; Lactation; Pesticide neurotoxicoIogy; amitraz; pesticide; animal experiment; controlled study; drug effect; female; health hazard; lactation; male; neurotoxicity; nonhuman; perinatal period; postnatal development; rat; Animals; Behavior, Animal; Female; Insecticides; Male; Rats; Rats, Wistar; Toluidines; Animalia; Rattus norvegicus